Using The Global Obstetric Fistula Electronic Registry to Digitalize Patient Records in Kathmandu Model Hospital - Pradhan, Hema Kumari; Dangal, Ganesh; Karki, Aruna; Shrestha, Ranjan; Bhattachan, Kabin; Poudel, Rekha; Bajracharya, Nishma; Tiwari, Kenusha Devi; Cochran, Seth; Michaelson, Bryony (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aim: The aim of the study was to collect and digitalize data of patients who underwent fistula repair at Kathmandu Model Hospital. Once data were collected, a Tableau dashboard was built to visualize the collected data and to share key insights. Methods: Operation Fistula built a digital version of Kathmandu Model Hospital’s Surgery Log, using a mobile data collection tool (CommCare). Researchers were trained on the data collection tool and provided with an electronic tablet device which hosted the application. Kathmandu Model Hospital then proceeded to input patient records, meanwhile providing Operation Fistula with key feedback to continue improving this process. Results: The results of this process have been threefold: facilitation of data collection, creation of an accurate database and provision of clear insights with access to data visualization dashboards. Conclusions: This study has shown the benefits of digitizing historical patient records using Operation Fistula’s Global Obstetric Fistula Electronic Registry (GOFER) platform. By creating an online database, this has the potential to be used for future academic research.